Aplikasi Game Edukasi Jelajah Pulau Sumatera Berbasis Android - Eka Chandra Ramdhani; Irfan Galuh (Paradigma, 2018)
See the development of games and multimedia at this time, and reinforced by the weak understanding of the younger generation of Indonesia about the culture of his own country. Therefore, the author took the initiative to create a mobile game that raised one of the culture of the country of Indonesia in general, especially for the provinces contained in the island of Sumatra. In the process of making this game the author uses Adobe Flash Professional Creative Suite 5.5 software for making all the characters, background and sound effects. Because in Flash itself already there are some sound library that can be used for the needs of the application in this game that the author made. For the programming language used the author uses only one programming language that is ActionScript 3.0. this programming language is functional enough to build a game, because it is supported with Object Oriented Programming which facilitate in making this game. In the latest version of Adobe Flash it is now possible to publish data into applications gained in instal on mobile devices, in this case android, making it possible to create android applications without having to abandon actionscript as the programming language used. It is expected that with this game will the user's understanding of cultural diversity in Indonesia, especially the island of Sumatra will be better understood and known